2019
DOI: 10.1002/alr.22430
|View full text |Cite
|
Sign up to set email alerts
|

Hemokinin‐1 stimulates C‐C motif chemokine ligand 24 production in macrophages to enhance eosinophilic inflammation in nasal polyps

Abstract: Background:The mechanisms underlying mucosal eosinophilia in chronic rhinosinusitis with nasal polyps (CRSwNP) remain poorly clarified. The nervous system and neuropeptides play an important role in the regulation of immune response. Herein we explore the expression and function of hemokinin-1 (HK-1), a newly identified tachykinin, along with its receptor neurokinin 1 receptor (NK1R) in CRSwNP. Methods:HK-1, NK1R, and C-C motif chemokine ligand 24 (CCL24) expression in nasal tissues (53 eosinophilic CRSwNP, 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…We found that 9 cytokines were significantly higher in the M2a hMdɸ-conditioned medium, while 15 cytokines were significantly higher in the M1 hMdɸ-conditioned medium (Table 2). Several of the 9 cytokines that were increased in the M2a hMdɸ-conditioned medium were previously reported to play a role in various inflammatory processes, including ocular inflammatory diseases and neurodegenerative diseases; these cytokines include CCL11 ( Deng et al, 2019 ; Mor et al, 2019 ; Segal-Salto et al, 2020 ; Shoji et al, 2017 ; Zeng et al, 2019 ), CCL13 ( El-asrar et al, 2019 ; Méndez-Enríquez et al, 2014 ; Mendez-Enriquez and García-Zepeda, 2013 ; Zeng et al, 2019 ), CCL17 ( Dai et al, 2015 ; Yu et al, 2011 ; Zeng et al, 2019 ), CCL23 ( Faura et al, 2020 ; Simats et al, 2018 ; Zeng et al, 2019 ), and CCL14 ( Liu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that 9 cytokines were significantly higher in the M2a hMdɸ-conditioned medium, while 15 cytokines were significantly higher in the M1 hMdɸ-conditioned medium (Table 2). Several of the 9 cytokines that were increased in the M2a hMdɸ-conditioned medium were previously reported to play a role in various inflammatory processes, including ocular inflammatory diseases and neurodegenerative diseases; these cytokines include CCL11 ( Deng et al, 2019 ; Mor et al, 2019 ; Segal-Salto et al, 2020 ; Shoji et al, 2017 ; Zeng et al, 2019 ), CCL13 ( El-asrar et al, 2019 ; Méndez-Enríquez et al, 2014 ; Mendez-Enriquez and García-Zepeda, 2013 ; Zeng et al, 2019 ), CCL17 ( Dai et al, 2015 ; Yu et al, 2011 ; Zeng et al, 2019 ), CCL23 ( Faura et al, 2020 ; Simats et al, 2018 ; Zeng et al, 2019 ), and CCL14 ( Liu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…72 Moreover, hemokinin-1 and neurokinin 1 receptor mRNA and protein expression were upregulated in eosinophilic and non-eosinophilic nasal polyps compared with control tissues, with eosinophilic polyps demonstrating a higher upregulation compared with that of non-eosinophilic polyps. 73 This neurogenic inflammation may contribute to the pathophysiology of CRS; hence, any targeted intervention may provide alternative therapeutic options. The pathophysiological pathways involved in CRS neuroinflammation are depicted in Figure 1.…”
Section: Chronic Rhinosinusitis (Crs)mentioning
confidence: 99%
“…showed that γδT cells were more abundant in the nasal mucosa of AR patients and may regulate innate and adaptive immune responses and their interaction. Additionally, Deng et al . observed that hemokinin‐1 (HK‐1) and its high‐affinity tachykinin receptor neurokinin 1 receptor (NK1R) were upregulated in human nasal polyps, and correlated with tissue eosinophilia in eosinophilic nasal polyps.…”
mentioning
confidence: 99%